2022
DOI: 10.1073/pnas.2113766119
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic determinism and stochasticity in antibody repertoires of clonally expanded plasma cells

Abstract: Significance B cell clonal selection and expansion from a genetically diverse antibody repertoire guides the immune response to a target antigen. It remains unclear if clonal selection and expansion follow any deterministic rules or are stochastic with regards to phenotypic antibody properties such as antigen-binding, affinity, and epitope specificity. We perform the in-depth genotypic and phenotypic characterization of antibody repertoires following immunization in mice. We identify the degree to wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 75 publications
3
11
0
Order By: Relevance
“…To profile B cell selection following serial protein immunizations, we immunized a cohort of 3-month-old (3m) male C57BL6 mice (n=5) with five successive injections of 10 μg of the extracellular domain of human TNFR2 mixed with 20 μg of the adjuvant monophosphoryl lipid A (MPLA). Our previous findings demonstrated that immunization of young mice with an immunogenic protein antigen (ovalbumin) results in highly expanded plasma cells within the bone marrow (Neumeier, Yermanos, et al 2021). For this study, we selected an antigen that has potentially reduced immunogenicity given its high sequence similarity (~61.3%) to the murine homologue of TNFR2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To profile B cell selection following serial protein immunizations, we immunized a cohort of 3-month-old (3m) male C57BL6 mice (n=5) with five successive injections of 10 μg of the extracellular domain of human TNFR2 mixed with 20 μg of the adjuvant monophosphoryl lipid A (MPLA). Our previous findings demonstrated that immunization of young mice with an immunogenic protein antigen (ovalbumin) results in highly expanded plasma cells within the bone marrow (Neumeier, Yermanos, et al 2021). For this study, we selected an antigen that has potentially reduced immunogenicity given its high sequence similarity (~61.3%) to the murine homologue of TNFR2.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, clonally expanded cells of IgM, IgG and IgA isotypes were still present in both organs (Figures S5, S6, S7). Previous single-cell antibody repertoire sequencing studies suggest a strong correlation between class-switched clones and the number of amino acid sequence variants existing within an individual clone (Neumeier, Pedrioli, et al 2021; Neumeier, Yermanos, et al 2021). Here, we observed that the number of cells for the most expanded IgG and IgA clones demonstrated a minor correlation with the number of amino acid variants, whereas some IgM clones contained a considerable number of amino acid variants (Figure 1F).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both these observations are in line with our simulations, as they show a large variability in subclone a nity. Recently, it has been reported in an OVA-immunized mouse model that a nities measured for plasma cells from blood samples do not correlate with clonal abundance on both a clone and subclone level 43 .…”
Section: Discussionmentioning
confidence: 99%